Occupational Safety and Health (K3), Discipline and Work Supervision on Employee Productivity - Suhardi, Suhardi; Rohaeni, Heni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to find out and analyze how the influence of occupational safety and health (k3), discipline and supervision on the productivity of employees in the production department at PT. Indonesian Smart Ambulance (API) Bekasi City. The sample in this study was 84 respondents and data collection used a questionnaire. The analysis technique in this study used linear regression. The results showed that the variables k3, discipline and supervision partially had a positive and significant effect on the productivity variable. Meanwhile, simultaneously, the variables k3, discipline and supervision have a positive and significant effect on the productivity variable.